2003
DOI: 10.22358/jafs/67719/2003
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR technique and its applications. State-of the-art

Abstract: The reverse transcription polymerase chain reaction (RT-PCR) is one of the most sensitive methods for the detection and quantitation of mRNA. It is widely used for quantification of mRNA levels and is useful tool for basic research, agriculture, medicine and biotechnology. Introduction of Real-time technique significantly improves rapidity, sensitivity, specificity and reproducibility of RT-PCR method. Real-time PCR detects and quantifies nucleic acids even from live and dead pathogens or cells. This review di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Unfortunately, in most of the studies, cDNA is prepared using kits containing a mixture of oligo(dT) and/or random hexamer primers [14,23,24], where oligo(dT) is not functional for lncRNA molecules without a polyA tail. It is well known that specific primers decrease background priming, but random and oligo(dT) primers maximize the number of mRNA molecules that can be analyzed from a small sample of RNA [25]. We observed that artificially adding polyA tails and then LincRNA-RoR NRON NTT using annealing anchor (dT) adapters (analogs of oligo(dT) primers) can help to quantify lncRNAs more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in most of the studies, cDNA is prepared using kits containing a mixture of oligo(dT) and/or random hexamer primers [14,23,24], where oligo(dT) is not functional for lncRNA molecules without a polyA tail. It is well known that specific primers decrease background priming, but random and oligo(dT) primers maximize the number of mRNA molecules that can be analyzed from a small sample of RNA [25]. We observed that artificially adding polyA tails and then LincRNA-RoR NRON NTT using annealing anchor (dT) adapters (analogs of oligo(dT) primers) can help to quantify lncRNAs more precisely.…”
Section: Discussionmentioning
confidence: 99%